The Strategy of Islamic Religious Education Teachers at Junior High Schools to Deal with Frustrated Students in Online Learning During the Covid_19 Pandemic - Nafiyanti, Septina (QUALITY, 2022)
Students at SMP Negeri 6 Jepara are used to receiving lessons directly from the teacher. They at school can interact directly with their friends. However, the Covid-19 Pandemic changed the learning that has been lived so far. Students take online learning. This learning had caused unpreparedness. Some students need help understanding the material being taught. Limited interactions. This condition caused frustration among some students. Handling and avoiding students from frustration requires the role of Islamic Religious Education teachers. This study describes the strategy of Islamic Religious Education teachers at SMP Negeri 6 Jepara as a decisive step for handling and avoiding student frustration with online learning. The approach used in this research is field research. The study found that Islamic Religious Education teachers at SMP Negeri 6 Jepara made lesson plans according to the conditions of the Covid-19 Pandemic, maintained student learning comfort, controlled student learning activity, provided student learning motivation, and increased students' spiritual intelligence.Strategi Guru PAI SMP Menghadapi Siswa Frustrasi Pembelajaran Dalam Jaringan Saat Pandemi Covid-19.Siswa di SMP Negeri 6 Jepara terbiasa menerima pembelajaran secara langsung dari guru. Mereka di sekolah dapat berinteraksi secara langsung dengan teman-temannya. Namun, Pandemi Covid-19 mengubah pembelajaran yang selama ini dijalani. Siswa mengikuti pembelajaran daring. Pembelajaran ini sempat menimbulkan ketidaksiapan. Sebagian siswa kesulitan memahami materi yang diajarkan. Interaksi yang dijalani terbatas. Kondisi itu sampai menimbulkan rasa frustrasi di kalangan sebagian siswa. Penanganan dan menghindarkan siswa dari frustrasi membutuhkan peran guru Pendidikan Agama Islam. Penelitian ini mendeskripsikan strategi guru Pendidikan Agama Islam SMP Negeri 6 Jepara sebagai langkah ampuh untuk penanganan dan menghindarkan siswa frustrasi dengan pembelajaran daring. Pendekatan yang digunakan dalam penelitian ini adalah penelitian lapangan. Hasil penelitian menemukan guru Pendidikan Agama Islam di SMP Negeri 6 Jepara membuat rencana pembelajaran sesuai kondisi Pandemi Covid-19, menjaga kenyamanan belajar siswa, mengontrol keaktifan belajar siswa, memberi motivasi belajar siswa, dan meningkatkan kecerdasan spiritual siswa.